2024
DOI: 10.3390/info15020088
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Students’ Hands-On Performance, Attitudes, and Usability with Arduino Modular Boards

Sokratis Tselegkaridis,
Theodosios Sapounidis

Abstract: Utilizing Arduino development boards for learning microcontroller circuits is a prevalent practice across various educational levels. Nevertheless, the literature offers limited insights into the impact of these boards on student performance and attitudes. Therefore, this paper aims to investigate the performance of 58 university students in learning microcontroller circuits with modular boards designed for Arduino through a series of 4 exercises. Specifically, students’ performance is assessed through pre-tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Moreover, studies have demonstrated the potential benefits of using Arduino in the educational process. For example, Tselegkaridis and Sapounidis [31] claim that modular boards may enhance code learning for Arduino. Based on them, there is a positive correlation between perceived usability and students' performance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have demonstrated the potential benefits of using Arduino in the educational process. For example, Tselegkaridis and Sapounidis [31] claim that modular boards may enhance code learning for Arduino. Based on them, there is a positive correlation between perceived usability and students' performance.…”
Section: Introductionmentioning
confidence: 99%